Hubungan Merokok Dengan Terbentuknya Lesi Kavitas Paru Pada Pasien Tuberkulosis RSUP H Adam Malik - Elisa Rinaldo Perdamenta; Henny Erina Saurmauli Ompusunggu; Joseph Partogi Sibarani (Fakultas Kedokteran Universitas Riau, 2023)
In 2022, 10,6 million people in the world were infected with tuberculosis and Indonesia ranks second. As many as 8 million of the world’s population died from tobacco smoking in 2021. Cavitary lung lesions are cavities filled with air in the lungs and smoking can directly damage lung parenchyma due its contents so tuberculosis patients who smoke are more risk of developing lung cavities. This study aims to determine association between smoking and formation of lung cavity. This study was an observational analytic study with case-control design using 80 samples consisting of 40 smoking and 40 non-smoker patients. Sample selection used purposive sampling technique and samples were collected from medical records in 2021. Data analysis used chi-square test. It was found that patients with lung cavity were 46,3% and patients who smoked and had lung cavity were 30%. Based on the result of data analysis, it can be concluded that there is a significant relationship between smoking and the formation of lung cavity lesions in tuberculosis patients at RSUP H Adam Malik with p = 0,014 (p < 0,05) and tuberculosis patients who smoke have a risk of 3,115 times to have lung cavity lesions (OR = 3,115).